The marginalized auxiliary particle filter - Fritsche, C.; Schon, T.B.; Klein, A. (2009 3rd IEEE International Workshop on Computational Advances in Multi-Sensor Adaptive Processing, 2009)
In this paper we are concerned with nonlinear systems subject to a conditionally linear, Gaussian sub-structure. This structure is often exploited in high-dimensional state estimation problems using the marginalized (aka Rao-Blackwellized) particle filter. The main contribution in the present work is to show how an efficient filter can be derived by exploiting this structure within the auxiliary particle filter. Based on a multi-sensor aircraft tracking example, the superior performance of the proposed filter over conventional particle filtering approaches is demonstrated.